State Bar Annual Meeting in Monterey - Watkins, Howard::::::::: (1988)
Fresno County Bar Association delegates: seated: John McGregor, Michael J.B. Smith, Jack Hames, and Judy Soley; Standing: Howard Watkins and Sandra Snyder